Computational analysis of binding between malarial dihydrofolate reductases and anti-folates. - Choowongkomon, K; Theppabutr, S; Songtawee, N; Day, N; White, N; Woodrow, C; Imwong, M (BioMed Central, 2010)
BACKGROUND: Plasmodium falciparum readily develops resistance to the anti-folates pyrimethamine and proguanil via a characteristic set of mutations in the dihydrofolate reductase (PfDHFR) gene that leads to reduced competitive drug binding at the enzyme's active site. Analogous mutations can be found in the DHFR gene in isolates of Plasmodium vivax (PvDHFR) although anti-folates have not been widely used for the treatment of this infection. Here the interactions between DHFR inhibitors and modelled structures of the DHFR enzymes of Plasmodium malariae (PmDHFR) and Plasmodium ovale (PoDHFR) are described, along with an investigation of the effect of recently reported mutations within PmDHFR. METHODS: DHFR models for PmDHFR and PoDHFR were constructed using the solved PfDHFR-TS and PvDHFR structures respectively as templates. The modelled structures were docked with three DHFR inhibitors as ligands and more detailed interactions were explored via simulation of molecular dynamics. RESULTS: Highly accurate models were obtained containing sets of residues that mediate ligand binding which are highly comparable to those mediating binding in known crystal structures. Within this set, there were differences in the relative contribution of individual residues to inhibitor binding. Modelling of PmDHFR mutant sequences revealed that PmDHFR I170M was associated with a significant reduction in binding energy to all DHFR inhibitors studied, while the other predicted resistance mutations had lesser or no effects on ligand binding. CONCLUSIONS: Binding of DHFR inhibitors to the active sites of all four Plasmodium enzymes is broadly similar, being determined by an analogous set of seven residues. PmDHFR mutations found in field isolates influenced inhibitor interactions to a varying extent. In the case of the isolated I170M mutation, the loss of interaction with pyrimethamine suggests that DHFR-inhibitor interactions in P. malariae are different to those seen for DHFRs from P. falciparum and P. vivax.